Nutrition support and nursing management for a patient with pressure injury (1例压力性损伤患者的营养干预及护理体会) - ZHANG Fengyao (张凤尧); GAO Chunli (高春利); ZHANG Ning (张宁); YUE Yuzi (岳玉姿); SHENG Yana (盛娅娜); TANG Ling (唐玲); ZHOU Jie (周洁) (中西医结合护理)
This paper summarized the nutrition support and nursing management for a patient with unstageable pressure injuries. Based on the assessment of wound condition, pain and nutrition, appropriate nutrition support combined with nursing interventions such as debridement and wound dressing change, Traditional Chinese Medicine nursing, pain management, in order to improve the wound healing. (本文总结1例不可分期压力性损伤患者的营养干预及相关护理技术。在完善伤口评估、疼痛评估和营养评估的基础上, 通过开展适宜的营养干预方案, 同时配合清创换药、中医护理技术、疼痛护理等干预措施, 促进压力性损伤伤口愈合。)